Embedding Technique versus Conventional Internal Limiting Membrane Peeling for Lamellar Macular Holes with Epiretinal Proliferation - Kanai, Masanori; Sakimoto, Susumu; Takahashi, Shizuka; Nishida, Kentaro; Maruyama, Kazuichi; Sato, Shigeru; Sakaguchi, Hirokazu; Nishida, Kohji (Ophthalmology retina, 2023)
To examine the outcomes of pars plana vitrectomy (PPV) with lamellar hole-associated epiretinal proliferation (LHEP) embedding and conventional internal limiting membrane (ILM) peeling for lamellar macular holes (LMHs) with LHEP. Retrospective observational study. Forty eyes of 39 consecutive patients with LMHs and LHEP who underwent 3-port PPV with a minimum follow-up of 3 months. We compared the results of eyes that underwent PPV with LHEP embedding and ILM peeling (group E) with those of eyes that underwent PPV with ILM peeling only (group I) from September 2010 to September 2021. We confirmed whether the LHEP was embedded using postoperative OCT in all the cases. Postoperative best-corrected visual acuity (BCVA) and the development of macular holes (MHs) were assessed. The mean patient age was 73.3 years. The mean follow-up duration was 23.1 months. There were 23 and 17 eyes in groups E and I, respectively. Preoperative BCVA (P = 0.774) and central retinal thickness (CRT) (P = 0.800) did not differ significantly between the 2 groups. The final BCVA in group E was better than that in group I (P = 0.059). The final CRT in group E was thicker than that in group I (P < 0.001). Postoperatively, a significant improvement in BCVA was observed in group E at 3 months (P = 0.001) and at the final visit (P < 0.001). None of the eyes in group E developed postoperative MHs, whereas 5 eyes in group I developed postoperative MHs. Pars plana vitrectomy using the LHEP embedding technique improved visual acuity significantly and yielded better anatomic outcomes than those with PPV using conventional ILM peeling; MH formation did not occur. Embedding LHEP is more effective than conventional surgical procedures for LMHs.